(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: During normal ageing, there are physiological changes especially in high energy demanding tissues including the brain and skeletal muscles. Ageing may disrupt homeostasis and allow tissue vulnerability to disease. To establish an appropriate animal model which is readily available and will be useful to test therapeutic strategies during normal ageing, we applied behavioral approaches to study age-related changes in memory and motor function as a basis for neuronal function in ageing in male Sprague Dawley rats. 3 months, n=5; 6 months, n=5 and 18 months, n=5 male Sprague Dawley Rats were tested using the Novel Object Recognition Task (NORT) and the Elevated plus Maze (EPM) Test. Data was analyzed by ANOVA and the Newman-Keuls post hoc test. The results showed an age-related gradual decline in exploratory behavior and locomotor activity with increasing age in 3 months, 6 months and 18 months old rats, although the values were not statistically significant, but grooming activity significantly increased with increasing age, p<0.05. Importantly, we established a novel finding that the minimum distance from the novel object was statistically significant between 3 months and 18 months old rats, (p<0.05) and this may be an index for age-related memory impairment in the NORT. Altogether, we conclude that the male Sprague Dawley rat show age-related changes in neuronal function and may be a useful model for carrying out investigations into the mechanisms involved in normal ageing